Formability in single point incremental forming: A comparative analysis of the state of the art. (January 2017) - McAnulty, Tegan; Jeswiet, Jack; Doolan, Matthew
Abstract: Single point incremental forming (SPIF) has higher formability limits than other sheet metal forming processes including stamping, and is therefore a desirable method of forming sheet metal components. To take advantage of this high formability it is necessary to understand how to maximise the limits through manipulation of parameters, increasing the likelihood of component success. In this paper, a systematic quantitative literature review was undertaken analysing experiments and results from 35 papers that studied the effect of process parameters on formability in SPIF. Collective results are presented regarding material thickness, tool diameter, tool shape and type, step down, feed rate, spindle speed and rotation direction, and some parameter interactions. The analysis provides evidence to support the hypothesis of an ideal operating range for each parameter and interdependency of parameters. A lack of focus in the literature on parameter interactions was found. A framework for important experimental parameters is proposed based on the review. Statement of originality: Quantitative analysis of research presented in the literature about parameter effects on formability in SPIF.